A Natural Low Phytic Acid Finger Millet Accession Significantly Improves Iron Bioavailability in Indian Women - Reddy, Bellam H. Rajashekar; Thankachan, Prashanth; Hatakayama, Masoami; Hiremath, Netravati; Moretti, Diego; Nanjareddy, Yellodu A.; Thumilan, Mathi B.; Ravikumar, Ramapura L.; Phadnis, Shamprasad; Bose, Beena; Poveda, Lucy; Kalaiah, Geetha; et al. (Frontiers in Nutrition, 2022)
Iron deficiency and anemia are common in low and middle income countries. This is due to a poor dietary iron density and low iron absorption resulting from the high inhibitory phytic acid content in cereal and millet-based diets. Here we report that a naturally occurring low phytic acid finger millet accession (571 mg.100g-1), stable across three growing seasons) with normal iron content (3.6 mg.100g-1), increases the iron absorption by three folds in normal Indian women. The accessions differing in grain phytic acid content, GE 2358 (low) and GE1004 (high) were selected from a core collection of 623 accessions. Whole genome re-sequencing of the accessions revealed significant single nucleotide variations segregating them into distinct clades. A non-synonymous mutation in EcABCC phytic acid transporter gene between high and low accessions could affect gene function and resulted in phytic acid differences. The highly sensitive dual stable-isotope erythrocyte incorporation method was adopted to assess the fractional iron absorption. The low phytic acid accession resulted in a significantly higher iron absorption compared with the high phytic acid accession (3.7% vs. 1.3%, p<0.05). Despite the low grain phytic acid content, GE 2358 did not show any reduction in growth and yield parameters compared with the widely cultivated variety. The low phytic acid accession could be effective in preventing iron deficiency in regions where finger millet is habitually eaten. With its low water requirement, finger millet leaves low environmental footprints and hence would be an excellent sustainable strategy to mitigate iron deficiency.